Design and Evaluation of a Web-Based Employee Performance Appraisal System Using Weighted Key Performance Indicators - Amanda Zachra Harahap; Rakhmat Kurniawan (Ali Institute of Research and Publication, 2026)
Employee performance appraisal in small and medium-sized organizations is often constrained by non-standardized indicators, fragmented records, and limited traceability of managerial decisions. This study designed and evaluated a web-based performance appraisal system for PT Naymas Mahkota Abadi using a weighted Key Performance Indicator (KPI) framework. Requirements were elicited through observation and structured interviews with the Human Resources Department and the Director. Six cross-divisional indicators were defined—attendance, work quality, work targets, attitude and behavior, teamwork, and initiative and responsibility—with weights totaling 100%. System construction followed Rapid Application Development and implemented role-based access for Human Resources, the Director, and employees. Functional verification used 20 black-box scenarios covering valid, invalid, boundary, and authorization conditions; all scenarios produced the expected outputs. A pilot User Acceptance Test with five users yielded an overall score of 90.8%. The system therefore demonstrated functional correctness and high initial user acceptance in the case organization. However, the uniform KPI weights, single-rater appraisal structure, and small acceptance-test sample limit broader generalization and do not establish improvements in employee performance. The contribution is a transparent, traceable, and operationally simple KPI configuration for centralized appraisal settings.